2016
DOI: 10.1088/1367-2630/18/3/033023
|View full text |Cite
|
Sign up to set email alerts
|

Generalised phase kick-back: the structure of computational algorithms from physical principles

Abstract: The advent of quantum computing has challenged classical conceptions of which problems are efficiently solvable in our physical world. This motivates the general study of how physical principles bound computational power. In this paper we show that some of the essential machinery of quantum computation-namely reversible controlled transformations and the phase kick-back mechanismexist in any operational-defined theory with a consistent notion of information. These results provide the tools for an exploration o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 33 publications
0
63
0
Order By: Relevance
“…The implication 'strong symmetry  permutability' follows immediately from the definitions. The implication 'strong symmetry  reversible controllability' was proved by Lee and Selby [63] using causality, purification, and the property that the product of two pure states is pure, which is guaranteed by our purity preservation axiom. Hence, we only need to prove the implications 'permutability  strong symmetry' and 'reversible controllability  strong symmetry'…”
Section: Appendix D Operational Features Of Doubled Quantum Theorymentioning
confidence: 93%
“…The implication 'strong symmetry  permutability' follows immediately from the definitions. The implication 'strong symmetry  reversible controllability' was proved by Lee and Selby [63] using causality, purification, and the property that the product of two pure states is pure, which is guaranteed by our purity preservation axiom. Hence, we only need to prove the implications 'permutability  strong symmetry' and 'reversible controllability  strong symmetry'…”
Section: Appendix D Operational Features Of Doubled Quantum Theorymentioning
confidence: 93%
“…Previous work [18] has shown that the conjunction of principles 1, 2, 3 and 5 implies the existence of reversible controlled transformations. These can be used to define oracles in a manner analogous to quantum theory [18].…”
Section: Setting Up the Problemmentioning
confidence: 95%
“…As such, one can classify theories according to their maximal order of interference, h. For example quantum theory lies at = h 2 and classical theory at = h 1. Higher order interference was initially formalised by Sorkin in the framework of quantum measure theory [29] but has more recently been adapted to the setting of generalised probabilistic theories in [3,18,19,33]. The most direct translation to this setting describes the order of interference in terms of probability distributions corresponding to the different experimental setups (which slits are open, etc) [18].…”
Section: Higher-order Interferencementioning
confidence: 99%
“…It is at the basis of an enormous variety of present and potential future applications [1], such as quantum communication [2,3], quantum computation [4][5][6] and protocols like entanglement swapping [7] or teleportation [8]. However, all these applications ultimately rely on interference and entanglement, which can be alternatively explained by theories sharing only some fundamental features with quantum mechanics, such as the superposition principle or probabilistic predictions for outcomes, and yet differing from it in other aspects [9][10][11][12]. In order to distinguish between quantum theory and such alternatives, one needs to design dedicated experiments.…”
Section: Introductionmentioning
confidence: 99%